Impact of Legal Jargon in English on Shaping Sri Lanka’s Legal System: An Experiential Survey on Stakeholder Perceptions - Hapuarachchi, B.A. (University of Jaffna, 2025)
Even after 75 years of independence, Sri Lanka still follows the legal system that it inherited from British colonial rule. Accordingly, the legal jargon used in Sri Lanka’s judiciary strictly adheres to colonial linguistic conventions that often involve Latin phrases. Yet, a fraction of Sri Lanka’s English language academic populace is engaged in a campaign to promote a brand of English known as Sri Lankan English formulated in their ivory towers, incorporating all types of interlanguage anomalies committed by Sri Lankans. So manipulative, they have even managed to influence Sri Lanka’s Ministry of Education to propagate that substandard variety of English within the national school system under the project “Speak English Our Way”. The category of English the so-called Sri Lankan English campaigners (who do not practice it within their families) attempt to promote under the popular term “decolonization” clashes with the linguistic conventions and language policies followed by Sri Lanka’s long-established legal institutions. Against this background, this paper investigates how the persistent use of colonial legal English has shaped the experiences and perceptions of key stakeholders including legal professionals, the judiciary, and the general public and what challenges the new category of English could pose on the common people. The exploratory study has a qualitative research design that involves in depth interviews, focus group discussions, and document analysis as data collection methods. Random sampling techniques such as snowball sampling and simple random sampling will be employed to select participants. As data analysis methods, thematic analysis and constant comparative methods will be employed. The gathering of the data and disclosure of information will be done while following ethical guidelines. Upon exploration, the findings will mainly contribute to processes related to language and legal policy reforms as well as to establishing a positive perspective for the general public in finding security in accessibility and comprehension of legal matters.
Keywords: Decolonisation; Colonial legal English; Sri Lankan English